2021
DOI: 10.1177/03635465211055476
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Ruptures in Middle-Aged Rats Heal Poorly Compared With Those in Young and Old Rats

Abstract: Background: Achilles tendon ruptures are painful and debilitating injuries and are most common in middle-aged patients. There is a lack of understanding of the underlying causes for increased rupture rates in middle-aged patients and how healing outcomes after a rupture might be affected by patient age. Therefore, the objective of this study was to define age-specific Achilles tendon healing by assessing ankle functional outcomes and Achilles tendon mechanical and histological properties after a rupture using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…However, validating these models with patient conditions should consider clinically relevantand preferably, clinically implementedfunctional outcome measures. Using our small animal dynamometer, we confirmed that a preclinical rat model (Freedman et al, 2016;Hillin et al, 2019;Huegel et al, 2019;Leahy et al, 2022) is a valid and relevant model to study the effects of Achilles tendon ruptures on plantar flexor function that directly translate similar measurements made in patients (Baxter et al, 2019(Baxter et al, , 2018Hullfish et al, 2019;Silbernagel et al, 2012). The angle-torque curves we measured in our non-surgically repaired rats compare favorably to the same measurements of plantar flexor function made in a cohort of patients treated non-surgically for an acute Achilles rupture (Figure 3).…”
Section: Discussionsupporting
confidence: 78%
“…However, validating these models with patient conditions should consider clinically relevantand preferably, clinically implementedfunctional outcome measures. Using our small animal dynamometer, we confirmed that a preclinical rat model (Freedman et al, 2016;Hillin et al, 2019;Huegel et al, 2019;Leahy et al, 2022) is a valid and relevant model to study the effects of Achilles tendon ruptures on plantar flexor function that directly translate similar measurements made in patients (Baxter et al, 2019(Baxter et al, , 2018Hullfish et al, 2019;Silbernagel et al, 2012). The angle-torque curves we measured in our non-surgically repaired rats compare favorably to the same measurements of plantar flexor function made in a cohort of patients treated non-surgically for an acute Achilles rupture (Figure 3).…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to humans, hindlimb tendons of rodents in advanced age regularly exhibit higher stiffness or elastic modulus (Wood et al 2011 ; Danos et al 2016 ; Wood and Brooks 2016 ; Leahy et al 2022 ). The magnitude of the increase is typically close to 50%.…”
Section: Methodsmentioning
confidence: 99%